1921-1950 Yıllarında Türkiye-Suriye İlişkilerinde Emlak-ı Metruke Sorunu - Pakize ÇOBAN KARABULUT (Gazi Akademik Bakış)
The first problem between Syrian and Turkey was initiated by the Ankara Agreement signed with France in 1921. With this treaty, the border of Syria was drawn with a ruler regardless of the ethnic and religious structure. In this case, between the Turkish and Syrian Arabs living in the region it has led to the derelict property and start experiencing the border problems in Turkey and Syria. Between the years 1921-1950, which is discussed in the article, there were important developments in the region and in the world. One of these developments is the Derelict Property problems between Syria and Turkey. The most important factor of unsolved problems between both countries has been the effectiveness of France in regional administration. As long as France is a mandatory state in the region, Syria has endeavored to have negative relations with both its neighbors and the Arab world. Therefore, the border issue and the continuation of experienced real estate shortage that occurred between Turkey and Syria was also reflected in the foreign policy of the two neighboring countries has led to the persistence of negative and conflicting foreign policy relations. In this study, both the 1921-1950 periods, the abandoned property issue occurred between Syria and Turkey was also examined and discussed the role of France in this process.